COVID-19, LOCKDOWN AND FAMILY LIFE IN A NEW REALITY - Haletska, Inna; Klimanska, Maryna; Perun, Mariia (PSYCHOLOGICAL JOURNAL, 2020)
The COVID-19 global pandemic, the risk of infection, lockdown, social and physical isolation, self-isolation, and unspecified period of quarantine have subjugated life on the Earth to the newest unprecedented rules. Permanent multi-day staying of families in a limited space and greater than usual proximity has become a great challenge, which has affected their mental health, psychological well-being and family relationships. The study aim was to determine the impact of the COVID-19 pandemic quarantine on the functioning and psychological well-being of families in Ukraine. The data were collected from the 14th to the 22nd of May, 2020 with the help of Google Forms via the social media. The study involved 238 parents aged 24 to 57 years. At the survey time, the quarantine has the form of a lockdown and lasted for more than two months, so the experience of the corona-virus infection threat was accompanied by severe restrictions against leaving home, distance work, a significant reduced income, and spontaneously organized distance learning for children, so parents were forced to teach their children. The following questionnaires were used for the data collection: the questionnaire on people’s lives in quarantine “Thermometer-COVID” (Haletska, Klymanska & Klimanska, 2020); a set of questionnaires to assess family relationships, parental effectiveness and children’s emotions during the epidemic (Gambin at al., 2020); Patient Health Questionnaire (modules PHQ-9 and GAD-7) and the Parental Stress Scale (Berry & Jones, 1995). Descriptive, variance, correlation, cluster and discriminate analyzes were used for the data analysis. The results show that quarantine has become a powerful stimulant of family unity: more than one-third of the respondents claimed that quarantine helped family members to become closer to each other (36,13%), a small percentage (7,14%) reported about worsened relationships, and 17,23% did about problems with order and control of their family situation. Increased tensions in marital relations occurred only at 6-8% of families, while improvements were observed at 20%. There were two key trends in the relationship with children: parents’ relationships with children became more tender and closer, while this emotionality led to inconsistencies in relationships with children, loss of patience, use of harsher punishments, or, conversely, excessive compliance. About one-third of the respondents had problems with the organization of their personal time, balancing of work and family responsibilities. About 80% of parents made conscious efforts to explain the situation with the epidemic and quarantine to their children; they accepted the negative emotions of children related to the quarantine (70,17%) and taught them preventive actions (80,25%). The average indicators of depressive and anxiety symptoms for all group corresponded to minimal depressive symptoms and moderate anxiety. There were no correlations between financial well-being, the number of people living together, the number of children and anxiety or depression. With the increased numbers of people living together and children in a family, the level of closeness with the children, satisfaction with the time spent together, the feeling of satisfaction with parenthood decreased, while the children (according to the parents’ opinion) had deeper depression, apathy, and sadness, were quick in tears and concentrated poorly their attention. In the case of family member’s poor education and/or financial status, a higher tendency to «conspiracy theories» of the virus origin (“corona-virus was created as a biological weapon with the aim of economic and political rearrangement of the world”) was observed. Those respondents who knew infected people felt a higher risk of corona-virus infection, adhered to preventive behaviour, considered corona-virus as more dangerous and information about it in media as more reliable, and were less pro-conspiracy theorists. They believed that quarantine helped families become closer, talked with children about the epidemic situation more often, but had lower tolerance to stress. Three types of family response to the quarantine situation were identified: “Resilience” (41%) - bringing family members closer, improvement of the family’s situation, despite the quarantine situation; “Distress” (33%) - tension and aggravation of conflicts, lack of control, disorganization and complication of family life; “Stability” (26%) - the family relationship without changes. There were difficulties in communicating with children, dissatisfaction with parenthood; children were more anxious, felt psychological tension and irritability in the families that reported about more family conflicts, worsened relationships, inability to balance work and family responsibilities in the new realities. The research results correspond to the findings presented at the scientific literature: a life-threatening event motivates significant actions and changes people’s lives, but does not determine clearly the pattern of reactions. The research results suggest that an important factor in psychological and family well-being is people’s ability to organize their lives in new conditions and circumstances, so it is important to prevent the destructive effects of stresses, to provide advice and assistance to people and families on adequate and effective planning and adjustment of life and conditions of daily life.